2017
DOI: 10.1111/jocd.12453
|View full text |Cite
|
Sign up to set email alerts
|

Cosmeceutical effect of ethyl acetate fraction of Kombucha tea by intradermal administration in the skin of aged mice

Abstract: This finding suggested that KEAf can be a suitable candidate as a cosmetic product to improve aging-related skin abnormalities and regeneration of aged skin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 35 publications
0
13
0
1
Order By: Relevance
“…TP has antioxidant, antibacterial, anticholesterolemic, and antidiabetic properties (Huang, Yan, et al., 2019; Jawad et al., 2019; Sarma et al., 2020; Shin et al., 2016; Zhong & Shahidi, 2012; Zhou et al., 2018). Many studies have shown that regular tea drinking can effectively alleviate aging (Fei et al., 2017; Li et al., 2019; Pakravan et al., 2018; Wang et al., 2019). Besides, TP can play an auxiliary role in cancer treatment (Ali et al., 2019; Yang et al., 2017).…”
Section: Introductionmentioning
confidence: 99%
“…TP has antioxidant, antibacterial, anticholesterolemic, and antidiabetic properties (Huang, Yan, et al., 2019; Jawad et al., 2019; Sarma et al., 2020; Shin et al., 2016; Zhong & Shahidi, 2012; Zhou et al., 2018). Many studies have shown that regular tea drinking can effectively alleviate aging (Fei et al., 2017; Li et al., 2019; Pakravan et al., 2018; Wang et al., 2019). Besides, TP can play an auxiliary role in cancer treatment (Ali et al., 2019; Yang et al., 2017).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, plant-based extracts or differential herbal formulations have been also exhaustively studied in several in vitro models, with different pharmacological actions on several mediators of skin elasticity, according to the following classification: Elastase inhibitory activity was determined after the use of the plant extracts prepared with Eugenia dysenterica [ 26 ], Gastrodia elata [ 27 ], Litchi sinensis [ 28 ], Magnolia officinalis [ 29 ], Malaxis acuminata [ 30 ], Manilkara zapota [ 14 ], Nephelium lappaceum [ 28 ], Phyllanthus emblica [ 14 ], Sclerocarya birrea [ 31 ], Sylibum marianum [ 14 ], Spatholobus suberectus [ 32 ], Tamarindus indica [ 28 ], and a polyherbal formulation containing Nyctanthes arbor-tristis leaf, unripe and ripe Aegle marmelos fruit pulp, and the terminal meristem of Musa paradisiaca extracts [ 33 ]; An increase in elastin synthesis or gene expression was observed after treatments with plant extracts of Piper cambodianum [ 34 ] and Bidens pilosa [ 35 ]; An increase in pro-collagen expression or synthesis was observed after treatments with plant extracts prepared from Alchemilla mollis [ 36 ], Azadirachta indica [ 37 ], Camellia sinensis [ 38 ], Citrus junus [ 39 ], Trapa japonica [ 40 ], and a mixture of plant extracts of Kochia scoparia and Rosa multiflora [ 41 ]; An increase in collagen synthesis or expression was observed after treatments with plant extracts of Andrographis paniculata [ 42 ], Cassia fistula [ 43 ], Camelia sinensis [ 44 ], Passiflora tarminiana [ 45 ], Physalis peruviana [ …”
Section: Skin Anti-aging Natural Products By Acting On the Skin Elast...mentioning
confidence: 99%
“…An increase in collagen synthesis or expression was observed after treatments with plant extracts of Andrographis paniculata [ 42 ], Cassia fistula [ 43 ], Camelia sinensis [ 44 ], Passiflora tarminiana [ 45 ], Physalis peruviana [ 46 ], Piper cambodianum [ 34 ], Solanum tuberosum [ 13 ], and Bidens pilosa [ 35 ];…”
Section: Skin Anti-aging Natural Products By Acting On the Skin Elast...mentioning
confidence: 99%
“…It is no longer enough to look good-it is also vital to delay ageing and prevent the appearance of illness. [78][79 [80] The chemical and pharmaceutical industries are well aware of this, and therefore, are under great pressure. Indeed, in recent years, a new term has been coined: "cosmeceutical" (cosmetic with therapeutic action) [81], which is the intersection of pharmacy and cosmetics.…”
Section: Present Scenario Of Herbal Product For Skin Carementioning
confidence: 99%